HUBUNGAN TEMAN SEBAYA DENGAN TINGKAT KEPERCAYAAN DIRI SISWA SD KELAS V DALAM BERBICARA DI DEPAN KELAS - Pratiwi, Mutia; Koswara Adiredja, Rajji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Public speaking is a essential skill that must be mastered by elementary school students, yet in reality, many students still experience anxiety and a lack of self-confidence. This study aims to determine the relationship between peer relationships and the self-confidence levels of fifth-grade students in public speaking within the classroom, conducted at an elementary school in the Leuwigoong area, Garut Regency. This research employs a quantitative correlational method. Data were collected through questionnaires distributed to fifth-grade students using a Likert scale. The data analysis technique utilized Partial Least Square – Structural Equation Modeling (PLS-SEM) assisted by SmartPLS 4.0 software. The results indicate that peer relationships have a positive and significant influence on students' self-confidence. In fact, a supportive environment from peers is proven to be a crucial supporting factor in reducing nervousness and increasing students' courage when expressing their opinions in front of the class. The implications of this study emphasize the importance of the teacher's role in creating a supportive classroom climate to build students' confident character.